Exploring the Complexity Levels of Discrete Manufacturing Processes. Issue 13 (2019) - Modrak, Vladimir; Soltysova, Zuzana
Abstract: Manufacturing processes are considered as dynamic systems and controlled objects that deal with scheduled/planned changes and unplanned changes due to several possible perturbations. This paper firstly describes potential measures of operational complexity of manufacturing processes. Subsequently, after comparison of their properties, one of them is selected as the most representative complexity measure. This operational complexity measure is based on the information theory and it evaluates the manufacturing processes based on the number of parts, machines and operations. The main goal of the paper is to outline a concept, by which complexity levels of discrete manufacturing processes can be explored. Accordingly, the paper proposes complexity categorization, based on which manufacturing processes can be categorized into the five complexity levels.